Impact of an Embedded Palliative Care Clinic on Healthcare Utilization for Patients With a New Thoracic Malignancy - Gast, Kelly C.; Benedict, Jason A.; Grogan, Madison; Janse, Sarah; Saphire, Maureen; Kumar, Pooja; Bertino, Erin M.; Agne, Julia L.; Presley, Carolyn J. (Frontiers in Oncology, 2022)
Introduction: Palliative care is beneficial for patients with advanced lung cancer, but the optimal model of palliative care delivery is unknown. We investigated healthcare utilization before and after embedding a palliative care physician within a thoracic medical oncology “onco-pall” clinic. Methods: This is a retrospective cross-sectional cohort study comparing healthcare outcomes in two cohorts: “pre-cohort” 12 months prior to and “post-cohort” 12-months after the onco-pall clinic start date. Patients were included if they had a new diagnosis of lung cancer and received care at The Ohio State University Thoracic Oncology Center, and resided in Franklin County or 6 adjacent counties. During the pre-cohort time period, access to palliative care was available at a stand-alone palliative care clinic. Outcomes evaluated included rates of emergency department (ED) visits, hospital admissions, 30-day readmissions, and intensive care unit (ICU) admissions. Estimates were calculated in rates per-person-years and with Poisson regression models. Results: In total, 474 patients met criteria for analysis (214 patients included in the pre-cohort and 260 patients in the post-cohort). Among all patients, 52% were male and 48% were female with a median age of 65 years (range 31-92). Most patients had non-small cell lung cancer (NSCLC - 17% stage 1-2, 20% stage 3, 47% stage 4) and 16% had small cell lung cancer. The post-cohort was older (median age 66 years vs 63 years in the pre-cohort (p-value: < 0.01)). The post-cohort had a 26% reduction in ED visits compared to the pre-cohort, controlling for age, race, marital status, sex, county, Charlson score at baseline, cancer type and stage (adjusted relative risk: aRR: 0.74, 95% CI: 0.58-0.94, p-value = 0.01). Although not statistically significant, there was a 29% decrease in ICU admissions (aRR: 0.71, 95% CI: 0.41-1.21, p-value = 0.21) and a 15% decrease in hospital admissions (aRR: 0.85, 95% CI: 0.70-1.03, p-value = 0.10). There was no difference in 30-day readmissions (aRR: 1.03, 95% CI: 0.73-1.45, p-value = 0.85). Conclusions: Embedding palliative care clinics within medical oncology clinics may decrease healthcare utilization for patients with thoracic malignancies. Further evaluation of this model is warranted.